Rapid evolution of latitudinal clines in growth and defence of an invasive weed - Yang, Yang (2021)
Re-establishment of heritable latitudinal clines in growth-related traits has been recognised as evidence for adaptive evolution in invasive plants. However, less information is known about latitudinal clines in defence and joint clinal evolution of growth and defence in invasive plants. We planted 14 native Argentinean populations and 14 introduced Chinese populations of Alternanthera philoxeroides in replicate common gardens in China. We investigated the latitudinal clines of traits related to growth and defence, and plasticity of these traits in relation to experiment site and soil nitrogen. We found that chemical defence decreased with latitude in introduced populations but increased with latitude in native populations. For growth rate, latitudinal clines were positive in introduced populations but nonexistent in native populations. There were also parallel positive latitudinal clines in total/shoot biomass and specific leaf area. Experiment site affected the occurrence or magnitude of latitudinal clines in growth rate, branch intensity and triterpenoid saponins concentration. Introduced populations were more plastic to experiment site and soil nitrogen than native populations. We provide evidence for rapid evolution of clines in growth and defence in an invasive plant. Altered herbivory gradients and trade-off between growth and defence may explain nonparallel clines between the native and introduced ranges.